ANALISA KELAYAKAN FINANSIAL USAHA PETERNAKAN BABI DI KABUPATEN MALANG - Karunia Setyowati Suroto; Ariani Trisna Murti (BUANA SAINS, 2022)
This study aimed to determine the income of farmers and analyze the financial feasibility of a pig farming business in Malang Regency. The method used in this research is a case study or case study method. The technique used in sampling is purposive sampling. Analyzing the data is by calculating the amount of income, R/C Ratio, Break Event Point (BEP), and Payback Period (PP). The results show that the average amount received from pig farming is Rp. 3.812.500.000 each year. Financial analysis shows the value of the R/C Ratio is 2.07, BEP production is 1.168.6 Kg, and BEP at Rp. 1.095.562, PP value is one year 29 days.